Paediatric rehabilitation engineering : from disability to possibility - Chau, Tom,; Fairley, Jillian, (Rehabilitation science in practice series., 2011)
"Written by international experts, this book provides an up-to-date synopsis of advances in pediatric rehabilitation engineering research. Offering a single comprehensive resource on the latest research findings, each chapter presents a different area of technology or the developments of particular clinical relevance to pediatric rehabilitation. The material within each chapter also includes a conceptual description of the technology or underlying scientific principles, followed by a synthesis of relevant literature, recent research advances, selected clinical case studies (where applicable), and perspectives for future directions"--Provided by publisher.